Neighbourhood composition dictates expression of soil legacy effects on plant growth - Kenneth J. Oppon; Charlotte Brown; Isaac Peetoom Heida; James F. Cahill (PLoS ONE, 2026)
Soil legacies, which reflect the influence of previous vegetation on soil biota and other properties, are increasingly recognized as drivers of current plant performance and community dynamics. Yet the expression of these legacies often depends on a focal plant’s immediate neighbours. We tested how soil biota from adjacent grassland and wolf-willow ( Elaeagnus commutata ) shrublands—representing a common shrub-encroachment transition in the northern prairies—affected the growth of Agrostis scabra when grown alone or with grass ( Festuca hallii ) or forb ( Geum triflorum ) neighbours. When grown alone, A. scabra responded differently across soil origins: grassland soil biota had a neutral effect, whereas wolf-willow strongly reduced growth. Neighbour presence modified these outcomes. In wolf-willow soils, the negative soil biota effect was no longer detectable with either neighbour individually, but re-emerged when both neighbours co-occurred, indicating non-additive interactions. In grassland soils, G. triflorum alone induced a negative effect that disappeared in the multi-neighbour treatment. Differences in soil chemistry, particularly the lower pH of wolf-willow soils, may have further shaped how microbial communities mediate plant responses. Overall, our findings demonstrate that soil biota effects on plant growth are not fixed by soil origin but are dictated by a plant’s neighbourhood composition, including neighbour identity, density, and their interaction with the abiotic context. Understanding these context-dependent soil legacies is essential for interpreting and predicting vegetation change and species coexistence across communities.